Encapsulating palladium nanoparticles inside ethylenediamine functionalized and crosslinked chlorinated poly(vinyl chloride) nanofibers as an efficient and stable heterogeneous catalyst for coupling reactions. (December 2020) - Qin, Min; Wang, Qingqing; Du, Yijun; Shao, Linjun; Qi, Chenze; Tao, Hongyu
Abstract: Palladium chloride and chlorinated poly (vinyl chloride) (CPVC) mixture were prepared into homogeneous solution, followed by electrospinning to make uniform nanofibers with average diameter of ~460 nm. Then, these composite nanofibers were treated in ethylenediamine solution to functionalize and crosslink the CPVC molecules inside the nanofibers to improve their chelating ability and solvent resistance. The functionalization and crosslinking of CPVC molecules inside composite nanofibers were confirmed by SEM, FT-IR, EA and PALS characterizations. The catalytic performance of these palladium encapsulated CPVC nanofibers (Pd@ACPVC) have been evaluated by the Heck and Sonogashira reactions. The catalysis results demonstrate that this Pd@ACPVC catalyst was very effective and stable to catalyze the coupling reaction of aromatic iodides with alkenes (Heck reaction) or phenyl acetylene (Sonogashira reaction) to afford the coupling products in moderate to excellent yields. Due to the regular fibrous structure, the Pd@ACPVC could be readily separated and recovered from reaction mixture. In addition, the Pd@ACPVC could be separately reused for 10 times for Heck reaction and 8 times for Sonogashira reaction without significant decrement of coupling yields. After careful investigation, the palladium leaching from Pd@ACPVC in the reuse procedure could be ascribed to the loss of chelating groups (amino groups) and expansion of free volume holes in the composite nanofibers. The excellent catalytic activity and stability of Pd@ACPVC could be attributed to the strong chelating ability of amino groups, encapsulation of palladium nanoparticles and ultrafine fiber. Graphical abstract: Image 1 Highlights: Pd nanoparticles were generated in crosslinked and aminated CPVC nanofibers. Pd nanoparticles were stabilized by chelating and capping effects. These nanofibers exhibited high activity and stability for coupling reactions. The activity decay was resolved by PALS and other common characterizations.